Effect of Information Literacy Skills on Clinical Decision-Making among Nurses - Riffat Mumtaz Malik; Muhammad Asif Naveed; Ghulam Murtaza Rafique (Journal of Information Management and Practices)
In the present technology–driven healthcare system, information literacy (IL) is a crucial skill that deserves attention and focus. As integral members of the medical profession, nurses must adopt IL skills to deliver high- quality patient-centered care by taking informed and evidence-based clinical decisions-making. To explore the effect of IL skills on clinical decision making (CDM) abilities of professional nurses; assess the relationship between these variables (IL skills and CDM) and to investigate the perceived IL skills and CDM abilities of nurses employed in private sector hospitals in Punjab, Pakistan. A quantitative nature survey was conducted using a questionnaire. Out of 500 conveniently selected participants, 306 responded. Data was analyzed using both descriptive and inferential statistics. Findings revealed that a positive correlation exists between information literacy skills and Clinical Decision Making of nurses. Regression analysis proved that there is a positive effect of IL skill on the CDM of nurses. Findings indicate that nurses possess strong IL skills and are competent in clinical decision making (CDM) abilities. The empirical evidence yielded by this investigation substantiates the hypothesis that a statistically significant and positive correlation was found between nurses’ IL skills and CDM capacities of nursing professionals. Nurses professionals having full command of IL skills can make sound and well- informed decisions in CDM process, which guarantees the delivery of safe healthcare services in the workplace.